PENGGUNAAN MEMBRAN KERAMIK BERBASIS ZEOLIT DAN CLAY DENGAN KARBON AKTIF SEBAGAI ADITIF UNTUK PENURUNAN KADAR FE DAN MN PADA AIR TANAH DAERAH BEKASI - Jevita Andini J. Ginting; Agus Setyo Budi; Esmar Budi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
Scarcity of water in major cities has given many problems to ground water reserves. Way that is widely used in water treatment are filtration using membrane technology. Membrane technology has several advantages, such as: the separation process can occur at room temperature and non destructive using. Membrane is a selective barrier between two phases (Fauzan, 2009). This research will make membrane with zeolit, clay and activated carbon as the basic material as aditive in the filtration process. The research focused on a membrane filtration process. Based on AAS result for groundwater that tested by membranes, we can conclude that membrane based on zeolith and clay with activated carbon as aditive can reduce the concentrartion of Fe and Mn in groundwater that taken from Bekasi. The highest Fe concentration reduction is about 49,59% and the highest Mn concentration reduction is about 56,21 %. Keywords: Membrane, Zeolite, Clay, Activated Carbon, Water Quality.